2022
DOI: 10.3389/fonc.2022.879281
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of 18F-NOTA-FAPI PET/CT in a Rat Model of Radiation-Induced Lung Damage

Abstract: In this study, we explore the diagnostic value of a novel PET/CT imaging tracer that specifically targets fibroblast activation protein (FAP), 18F-NOTA-FAPI, in a radiation induced lung damage (RILD) rat model. High focal radiation (40, 60, or 90 Gy) was administered to a 5-mm diameter area of the right lung in Wistar rats for evaluation of RILD induction. Lung tissues exposed to 90 Gy radiation were scanned with 18F-NOTA-FAPI PET/CT and with 18F-FDG. Dynamic 18F-NOTA-FAPI PET/CT scanning was performed on day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Qin et al [ 10 ] monitored the development of lung tissue damage after radiotherapy and determined the uptake of [ 18 F]FAPI in the stage of pulmonary fibrosis in a rat model, which is consistent with the results of previous studies. However, no studies have focused on the acute inflammatory stage.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…Qin et al [ 10 ] monitored the development of lung tissue damage after radiotherapy and determined the uptake of [ 18 F]FAPI in the stage of pulmonary fibrosis in a rat model, which is consistent with the results of previous studies. However, no studies have focused on the acute inflammatory stage.…”
Section: Introductionsupporting
confidence: 80%
“…Fibroblasts are persistently activated in chronic fibrosis and tumor fibrosis, but not in acute inflammation [ 9 ]. In the study by Qin et al [ 10 ], [ 18 F]FAPI uptake was observed on day 7 in the 90 Gy group with foamy macrophages and slight collagen deposition present which should be classified as chronic inflammatory phase. The reason for the inconsistency with our results may be the difference in radiation dose and the radiosensitivity of different murine.…”
Section: Discussionmentioning
confidence: 98%
“…Although there have been no systematic reports of FAP expression in granulomas, granulomatous lesions may show high FAP expression. Regarding radiation pneumonitis, Qin et al reported increased FAP expression and FAPI uptake in a rat model of radiation-induced lung damage (20). Further, R€ ohrich et al reported increased uptake in fibrotic lung disease (21).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding radiation pneumonitis, Qin et al. reported increased FAP expression and FAPI uptake in a rat model of radiation-induced lung damage ( 20 ). Further, Röhrich et al.…”
Section: Discussionmentioning
confidence: 99%
“…For example, for longer FAP tracking 18 F-based radiotracers are considered to be more preferable compared to the 68 Ga-based ones [136]. The recently developed fluorine-18-based markers targeting FAP have been tested in the rat model of radiation-induced lung damage [190] and in tumour uptake models [191,192], including the mice model of breast cancer [193].…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%